Characteristics of aufeis for the Penzhina River basin derived from Landsat images (2013-2019) - Makarieva, Olga; Shikhov, Andrey; Ostashov, Andrey; Nesterova, Nataliia; Semakina, Anastassiya (PANGAEA, 2020)
Present-day aufeis dataset was created by Landsat-8 OLI images for the period 2013-2019. Each aufeis was delineated by satellite images as polygon. Cloud-free Landsat images are obtained immediately after snowmelt season, to detect the highest possible number of aufeis. Critical values of Normalized Difference Snow Index (NDSI) were used for semi-automated aufeis detection. However, a detailed expert-based verification was performed after automated procedure, to distinguish snow-covered areas from aufeis and cross-reference historical and satellite-based data collections. According to Landsat data, the number of aufeis reaches 2758, with their total area about 1147.1 km². The difference between the Cadastre (1958) and the satellite-derived data may indicate significant changes of aufeis formation environments.
Keywords: aufeis; Chukitka; Historical Cadastre; Landsat